Ancaman Penjatuhan Hukuman Pemiskinan Pelaku Tipikor Di Indonesia Sebagai Upaya Preventif : The Threat of Imposing Asset Forfeiture on Corruption Offenders in Indonesia as a Preventive Measure - Muhammad Dliyaul Lami' (CLEAR: Criminal Law Review, 2023)
Throughout 2021, the Indonesian state's losses reached Rp. 62.93 trillion and asset recovery about 1.4 trillion. Impoverishment punishment hoped to provide a deterrent effect due to criminal acts of corruption. Fiqh Jinayah has rules that can be imposed on perpetrators of crimes such as Hudud, Qishash, Kafarat, and Ta'zir. Corruption is included in the ta'zir finger because the punishment for corruption is not stipulated in the Al-Quran and Hadith. The focus of the problems studied are: 1). How is the construction of impoverishment punishment as a preventive measure for corruption offenders in Indonesia? 2). How is the construction of impoverishment punishment, from the perspective of Fiqh Jinayah? To find out the problems in this research, the researcher uses a type of normative legal research. Thus, the design of the procedure for imposing impoverishment penalties for corruption offenders has been carefully regulated as set forth in Law no. 20 of 2001 on changes to Law no. 31 of 1999. The imposition of impoverishment sentences aims to reduction, limitation, and prevention to the perpetrators so that there is no repetition of the crime. This is in line with the characteristics of corruption seen from Fiqh Jinayah view. Therefore, the imposition of impoverishment sentences for perpetrators of corruption in Indonesia can be included in the category of jarimah ta'zir which has certain limits on the number of sentences and the material prescribed in Fiqh Jinayah. Sepanjang tahun 2021 kerugian perekonomian negara Indonesia mencapai Rp. 62,93 triliun dan asset recovery masih menyentuh diangka 1,4 triliun. Maka dengan adanya hukuman pemiskinan diharapkan bisa memberikan efek jera dan terpenuhinya perekonomian negara akibat tindak pidana korupsi. Fiqh Jinayah terdapat aturan yang bisa dikenakan kepada pelaku tindak pidana seperti Hudud, Qishash, Kafarat, dan Ta’zir. Korupsi termasuk ke dalam jarimah ta’zir karena korupsi hukumannya tidak memiliki ketetapan dalam Al-Quran dan Hadis. Fokus masalah yang diteliti yakni: 1). Bagaimana konstruksi penjatuhan hukuman pemiskinan sebagai upaya preventif bagi pelaku tipikor di Indonesia? 2). Bagaimana konstruksi penjatuhan hukuman pemiskinan itu, dalam perspektif Fiqh Jinayah? Untuk mengetahui permasalahan dalam penelitian tersebut peneliti menggunakan jenis penelitian hukum normative. Dengan demikian, perancangan mengenai prosedur penjatuhan hukuman pemiskinan bagi pelaku tipikor telah diatur dengan cara seksama yang termaktub dalam  UU No. 20 Tahun 2001 atas perubahan UU No. 31 Tahun 1999. Penjatuhan hukuman pemiskinan bertujuan untuk memberikan pengurangan, pembatasan, serta pencegahan kepada pelaku agar tidak terjadi pengulangan tindak pidana. Hal ini selaras dengan adanya ciri-ciri tindak pidana korupsi yang dilihat dari kacamata Fiqh Jinayah Maka dari itu, penjatuhan hukuman pemiskinan bagi pelaku korupsi di Indonesia bisa termasuk kedalam kategori jarimah ta’zir yang mana memiliki kepastian batasan pada jumlah hukuman serta materi yang disyariatkan dalam Fiqh Jinayah.